Triiodothyronine and dexamethasone alter potassium channel expression and promote electrophysiological maturation of human-induced pluripotent stem cell-derived cardiomyocytes. (December 2021) - Wang, Lili; Wada, Yuko; Ballan, Nimer; Schmeckpeper, Jeffrey; Huang, Jijun; Rau, Christoph Daniel; Wang, Yibin; Gepstein, Lior; Knollmann, Bjorn C.
Abstract: Background: Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) have emerged as a promising tool for disease modeling and drug development. However, hiPSC-CMs remain functionally immature, which hinders their utility as a model of human cardiomyocytes. Objective: To improve the electrophysiological maturation of hiPSC-CMs. Methods and results: On day 16 of cardiac differentiation, hiPSC-CMs were treated with 100 nmol/L triiodothyronine (T3) and 1 μmol/L Dexamethasone (Dex) or vehicle for 14 days. On day 30, vehicle- and T3 + Dex-treated hiPSC-CMs were dissociated and replated either as cell sheets or single cells. Optical mapping and patch-clamp technique were used to examine the electrophysiological properties of vehicle- and T3 + Dex-treated hiPSC-CMs. Compared to vehicle, T3 + Dex-treated hiPSC-CMs had a slower spontaneous beating rate, more hyperpolarized resting membrane potential, faster maximal upstroke velocity, and shorter action potential duration. Changes in spontaneous activity and action potential were mediated by decreased hyperpolarization-activated current (If ) and increased inward rectifier potassium currents (IK1 ), sodium currents (INa ), and the rapidly and slowly activating delayed rectifier potassium currents (IKr and IKs, respectively). Furthermore, T3 + Dex-treated hiPSC-CM cell sheets (hiPSC-CCSs) exhibited a faster conduction velocity and shorter action potential duration than the vehicle. Inhibition of IK1 by 100 μM BaCl2 significantly slowed conduction velocity and prolonged action potential duration in T3 + Dex-treated hiPSC-CCSs but had no effect in the vehicle group, demonstrating the importance of IK1 for conduction velocity and action potential duration. Conclusion: T3 + Dex treatment is an effective approach to rapidly enhance electrophysiological maturation of hiPSC-CMs. Graphical abstract: Unlabelled Image Highlights: T3 + Dex treatment increases INa, IK1, IKr and IKs and reduces If in hiPSC-CMs. T3 + Dex treatment shortens action potential in hiPSC-CMs. T3 + Dex treatment increases conduction velocity in hiPSC-CM cell sheets. T3 + Dex treatment enhances the electrophysiological maturation of hiPSC-CMs.